Extrusion processing of sago (metroxylon sagu rottb.) starch for thermoplastic starch production preliminary investigation - Muca, Jude Carlo Jalla (2009)
To produce biodegradable plastics from a renewable resource such as sago starch, a single-screw extrusion system to make thermoplastic sago starch (TPS) polymers was designed and fabricated. The single-screw extruder design was made in consultation with a practicing mechanical engineer. The extruder design was made in consultation with a practicing mechanical engineer. The extruder-cooker had three zones: the feeding, melting/transition, and the metering sections. It could be operated on either of two speeds 160 rpm and 190 rpm, and had heating elements on the external barrel surface extending from the melting zone to the beginning of the metering zone. Blends of sago starch, water, and glycerol (20% and 40%) w/w) were fed into the extruder, and the thermoplastic starch extrudates were preliminary investigated using tensile strength, biodegradability, and disintegration in water. TPS samples with 20% glycerol and extruded at a temperature of 900C had the greatest tensile strength at break (1.63MPa). The tensile strengths at break of TPS samples with 20% glycerol exhibited an inverse relationship with barrel temperature. On the first 5 days of preliminary biodegradation tests, the thermoplastic starch material showed integrity, which is a sign of the success in the plastification by the fabricated extruder-cooker, samples were generally resistant to disintegration in water as evaluated visually. The extrudates were considered for further tests as to their further utilization. It is recommended that further biodegradation tests be done to confirm biodegradability
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2009
Keywords: Thermoplastic starch; Biodegradable plastics; Tensile strength at break; Biodegradation; Single-screw extruder; Renewable resources; Plastics; Cooperative Research Center (CRC).; Starch-based films; Purchase bags; Plastiticizers; Amylose contents; Thermoplastic polyesters; Starch